Wiley Encyclopedia of Chemical Biology 2008
DOI: 10.1002/9780470048672.wecb641
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Mimics: Cyclic Compounds

Abstract: Compounds that contain phosphate and diphosphate moieties are not ideal biologic probes. Not only does their ionic character inhibit cell membrane permeability, but also, once inside a cell, the ester and the anhydride functionalities are likely targets for enzymatic cleavage. Thus, replacements for the phosphate motif are important as enzyme inhibitors, DNA or RNA analogs, phospholipid mimics, and phosphorylated metabolite analogs. To date, several classes of phosphate mimics have been developed that have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…For instance, 65 is an efficient inhibitor of MurC (UDP-N-acetylmuramate/L-alanine ligase) [139] and 66 e of MurG [189]. It should be emphasized that the 4-thiazolidinone and rhodanine cores are treated as novel phosphate mimics [190] (Scheme 34).…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…For instance, 65 is an efficient inhibitor of MurC (UDP-N-acetylmuramate/L-alanine ligase) [139] and 66 e of MurG [189]. It should be emphasized that the 4-thiazolidinone and rhodanine cores are treated as novel phosphate mimics [190] (Scheme 34).…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…For example, the use of derivatives of the phosphate ester, such as phosphonates and thiophosphonates, has been a widespread tactic to bring untested functionalities into molecules. 2 d ,3…”
Section: Introductionmentioning
confidence: 99%
“…7B ). Previous studies have shown that phosphate groups can be mimicked by neutral scaffolds ( 41 ). For instance, a neutral diphosphate mimic has been demonstrated to inhibit the activity of human O-GlcNAc transferase (OGT), an enzyme that recognizes UDP-GlcNAc harboring a diphosphate group ( 42 ).…”
Section: Resultsmentioning
confidence: 99%